Determining Survivals of Platelets and Fibrinogen Using HAP an Interactive Hemostasis Analysis Computer Program - Abramson, Mark J; Stein, Sidney F; Goldstein, J H (Thrombosis and Haemostasis, 1981)
An interactive computer program is described which permits computation of platelet survivals based on the gamma function model of Murphy. An additional feature permits the treatment of other labelled proteins, e. g. fibrinogen, disappearing via an exponential process. The program requires no prior computer background and typical determinations of survivals can be effected in about five min, representing a substantial enhancement to the gamma function program as currently provided by the International Committee for the Standardization of Hematology. Provision has also been made for modifications to meet individual needs. The program is described in sufficient detail, including sample calculations, to permit evaluation for possible applications.
Keywords: Platelet survival; Fibrinogen survival; Computer program; Automated